Evaluating the Effectiveness of Uterine Condom Balloon Tamponade Training in Reducing Postpartum Hemorrhage Outcomes in Tertiary Care Hospitals of Peshawar, Khyber Pakhtunkhwa, Pakistan - Nusrat Ara; Haris Shoaib Khan; Bibi Sultania (Dialogue Social Science Review (DSSR), 2025)
Postpartum hemorrhage (PPH) remains a major contributor to maternal mortality and morbidity globally, disproportionately affecting low-resource settings. While Uterine Condom Balloon Tamponade (UCBT) offers a crucial, non-surgical intervention for managing severe PPH, its effective implementation hinges on adequate training for healthcare providers. This quasi-experimental study assessed the effectiveness of a targeted educational intervention on improving healthcare providers' knowledge and practical skills in UCBT application within tertiary care hospitals in Peshawar, Pakistan. Fifty-four participants took part in a pretest-posttest study design, receiving structured UCBT training. Results demonstrated significant improvements in both knowledge and practice post-intervention. Mean knowledge scores increased significantly from 4.28 to 7.80 (p<0.05), and the UCBT implementation rate rose substantially from 24% to 64.8%. These findings highlight the importance of focused UCBT training programs for enhancing maternal health outcomes and strongly advocate for the integration of UCBT education into standard obstetric training curricula. In conclusion, this study provides compelling evidence that targeted training significantly improves healthcare providers' UCBT competence, suggesting that widespread implementation of such programs could substantially improve PPH management and contribute to a reduction in maternal mortality in similar contexts.